Implementasi Tema Arsitektur NeoVernacular Pada Pusat Kerajinan Tenun Di Desa Pejeng Kangin: bahasa indonesia - I Gede Ardika; Made Suryanatha Prabawa; I Ketut Sugihantara; Anak Agung Bagus Bayu Anggawirya (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2024)
In Bali, proposing is a traditional craft that has been practiced for a long time. Weaving is now more than just a side job or a way to fill time, but has also developed into a creative industry. The process of intertwining warp and weft threads is known as monten. The weft threads are attached to the warp threads and attached to the loom, and the warp threads which, when connected, will produce a motif. This research uses three Literary Study research methods. The method for analyzing data systematically uses a summarized version of existing data, such as books, journals, or articles, in the classroom. Direct interviews with related parties in the Balinese endek woven fabric industry were used as a data collection method. Precedent Study, Surveying observers regarding architectural approaches for planning and designing a weaving craft center in Pejeng Kangin village and indirectly searching for other objects outside Bali via the internet are the methods used to collect data. The planning and design of the Weaving Craft Center in Pejeng Kangin Village, Bali has objectives that include helping tourism development and providing new innovations in the field of woven fabric centers, as well as providing learning about fabric processing. The weaving craft center in Pejeng Kangin village can have a positive impact on the community in the surrounding Pejeng Kangin village and help develop tourism, especially in Pejeng Kangin village.